2020
DOI: 10.1097/md.0000000000020082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of 6-thioguanine in the treatment of childhood acute lymphoblastic leukemia

Abstract: Background: To systematic review the efficacy and safety of 6-thioguanine (6-TG) in the substitute of 6-mercaptopurine (6-MP) in the treatment for patients with childhood acute lymphoblastic leukemia (ALL) in the maintenance phase, and to explore its clinical application value. It provides theoretical guidance for the maintenance treatment of ALL in children from the perspective of evidence-based medicine. Methods: By means of computer retrieval, Chinese databases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Recent studies have indicated that leukopenia, neutropenia, thrombocytopenia, and elevated transaminase are all remarkably correlated with the dose of mercaptopurine drugs. The same idea can be found in the study put forward by Chen et al [46]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have indicated that leukopenia, neutropenia, thrombocytopenia, and elevated transaminase are all remarkably correlated with the dose of mercaptopurine drugs. The same idea can be found in the study put forward by Chen et al [46]. They have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 77%
“…31 TMZ is approved for the treatment of multiple malignancies including glioblastoma, while 6TG is currently used in hematologic malignancies. 32 , 33 To assess the impact of TMZ and 6TG on our mouse cellular models, we performed a loss-of-function genetic screen using a custom pooled CRISPR library targeting 488 genes involved in DNA damage response (DDR) and repair pathways ( Table S1 ). This approach allowed the identification of genes that, when disabled, lead to drug resistance in the mouse CRC CT26 cell model.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct from other breast cancer, the incidence of triple-negative breast cancer in young women is also higher, coupled with the larger size of the tumor. Relatively, TNBC develops rapidly and its outcome and morbidity within 5 years are poor and very high, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 99%